Vroom en daarom rechtzinnig. Brümmer over het primaat van de geloofsbeleving - Van den Brink, Gijsbert (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
Pious and therefore orthodox. Brümmer on the primacy of faith experience In a new (as yet unpublished) manuscript Vincent Brümmer’s academic work takes a surprising turn, in that he moves from philosophical theology to historical theology. This paper shows that behind Brümmer’s recent historical work (a sample of which has already been published in Brümmer 2010) a strong systematic concern can still be discovered: Brümmer wants to show how the theology of Nicolaas Hofmeyr (1827-1909), Andrew Murray (1828-1917) and their followers was largely determined by their spirituality (which focused on the experience of a personal relationship with God through Christ in the Spirit) rather than the other way around. As mystical theologians, and contrary to the contemporary (Kuyperian and Princetonian) confessionalists, piety was more important to them than orthodoxy – and this is indeed what we should learn from them. In response to this, I suggest that the relation between piety and orthodoxy is more of a synthetical than of an antithetical nature.